Multi-omics profiling reveals the role of 4-ethylbenzoic acid in promoting proliferation and invasion of cervical cancer - Huang, Xiaoling; Lu, Shan; Li, Xiaoge; Wu, Jin; Zu, Qiao; Duan, Zhaoning; Luo, Ming; Jia, Ying (Frontiers in Medicine, 2025)
BackgroundCervical cancer (CC) is a global health challenge, ranking fourth among cancers in women. Microbiome–metabolome interactions influence human papillomavirus (HPV) associated carcinogenesis, but specific microbial metabolites driving malignant progression remain undefined. This study aimed to identify potential biomarkers for distinguishing CC, and further explore their role in the progression of CC.MethodsNon-targeted metabolomics was employed to profile alterations in the vaginal microenvironment across clinical cohorts, including individuals with CC, individuals with cervical intraepithelial neoplasia (CIN), HPV-positive individuals, and HPV-negative individuals. Targeted metabolomics was then used to confirm the expression of 4-ethylbenzoic acid (4-EA) levels and its role in CC was explored using cell counting kit-8, 5-ethynyl-2′-deoxyuridine, colony formation, transwell, and wound healing assays. Proteomics was used to investigate the effects of 4-EA on CC cells.ResultsThe metabolic profiles of vaginal secretions in the CC group differed significantly from those in the other three groups. Untargeted metabolomics identified 27 CC-specific metabolites (VIP > 2, p < 0.05), revealing a marked elevation of 4-EA and its close relationship with vaginal microorganisms. Clinico-pathological correlations revealed progressive 4-EA accumulation across the cervical carcinogenesis stages. Additionally, 4-EA promoted the proliferation, migration, and invasion of CC cells in vitro. Proteomic reprogramming of CC cells following 4-EA treatment identified 14 highly expressed proteins associated with poor prognosis.ConclusionThis multi-omics investigation identified 4-EA as a novel candidate metabolite and a potential biomarker of CC. Identification of key proteins may provide new insights for interventions targeting the development of CC.